1989
DOI: 10.2105/ajph.79.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Results of routine restaurant inspections can predict outbreaks of foodborne illness: the Seattle-King County experience.

Abstract: To analyze the association between the results of routine inspections and foodborne outbreaks in restaurants, we conducted a matched case-control study using available data from Seattle-King County, Washington. Case restaurants were facilities with a reported foodborne outbreak between January 1, 1986 and March 31, 1987 (N=28). Two control restaurants with no reported outbreaks during this period were matched to each case restaurant on county health district and date of routine inspection (N=56). Data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 7 publications
0
45
0
Order By: Relevance
“…In Seattle-King County, WA, viola tions of temperature control of potentially hazardous food were most strongly associated with outbreaks (14). In Los Angeles County, CA, outbreaks were associated with in correct storage of food, reuse of food, and any food pro tection violation (3).…”
Section: Discussionmentioning
confidence: 99%
“…In Seattle-King County, WA, viola tions of temperature control of potentially hazardous food were most strongly associated with outbreaks (14). In Los Angeles County, CA, outbreaks were associated with in correct storage of food, reuse of food, and any food pro tection violation (3).…”
Section: Discussionmentioning
confidence: 99%
“…Failure to comply with food hygiene standards have been shown to predict outbreaks of food borne illness [17]. In theory, it should be straightforward to prevent outbreaks by giving appropriate advice but in practice this can prove difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The bakery was inspected on 14 August and production of custard slices discontinued. The first Outbreak Control Team was convened on 17 August and advice issued to bakery staff on personal hygiene, appropriate cleaning procedures for equipment and kitchen surfaces, use of separate mixing bowls for products made from raw ingredients and the substitution of pasteurized egg for M. R. Evans and others recipes containing shell egg. By 28 August, no new cases with an onset after 10 August had been identified and the outbreak was considered to be under control.…”
Section: Outbreaksmentioning
confidence: 99%
“…(Cruz et al, 2001). Irwin et al (1989) reported a correlation between restaurant inspection scores and foodborne illness in Seattle-King County,…”
Section: Problems With Inspection Disclosurementioning
confidence: 99%